International Portfolio Diversification in Emerging Markets: 'A UK Perspective' - Khan, Shakeel (2008)
The study explores key issues of international portfolio diversification by UK investors, particularly in emerging markets of India, China, Korea and Brazil. With the expansion of the emerging markets on the global financial frontiers, it is imperative for investors to look beyond their own home countries (developed economies like the UK) for increasing their returns and reduce the risk (standard deviation) involved in within country portfolio diversifications. Lack of correlation between developed and emerging economies makes it even more desirable for the western investors to diversify their portfolio in emerging economies for profit enhancement. This present study analyzes how the UK investors stand to benefit from diversifying their business portfolios in emerging markets. The data for analysis are daily indexes from FTSE for the markets under study for ten year period from January 1998 to December 2007. The study examines various portfolios containing returns and risk of individual markets individually and in pairs. This is done to analyze efficiency frontiers (levels of returns and risks) of different compositions of portfolios (individual and dyads) obtained for UK investors by countries. Two-country portfolios are created by using weighted index and their combinations to look deeper into ratios of returns and risks for each market. International portfolio investment in emerging markets is an encouraging and beneficial strategy for UK Investors. On the basis of this study with its limited scope and data size, suggestions have been made for further research on the subject and recommendations have been made for applications of the results for international portfolio diversifications in emerging markets.